OCULAR COMPLICATIONS IN CUTANEOUS LUPUS ERYTHEMATOSUS : A SYSTEMATIC REVIEW - Yovita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Dry eye disease (DED) is a multifactorial disorder of the ocular surface characterized by disruption of tear film homeostasis, instability of the tear film, and inflammation of the ocular surface. Although the precise mechanism of action is still inadequately understood, numerous studies have demonstrated that IPL has the potential to alleviate both the signs and symptoms of dry eye. The aim: This article showed ocular complications in cutaneous lupus erythematosus. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 115 articles, whereas the results of our search on SagePub brought up 97 articles. The results of the search conducted for the last year of 2013 yielded a total 32 articles for PubMed and 26 articles for SagePub. In the end, we compiled a total of 27 papers, 14 of which came from PubMed and 13 of which came from SagePub. We included nine research that met the criteria. Conclusion: SLE ocular symptoms can indicate active SLE. In daily ophthalmology, SLE should be considered a differential diagnosis, especially for symptoms. Systemic treatment is based on ophthalmology. SLE management requires division and medical field collaboration. Systemic treatment includes antimalarials, corticosteroids, immunomodulators, and biologics.